Pravni vidiki tržne dejavnosti javnih zavodov - Pirnat, Rajko (Podjetje in delo, 2020)
The author analyses the legal nature of activities of public institutions regarding the relation between public service and market (economic) activity. By defining economic and non-economic activity in terms of EU law, the author concludes that many activities that represent non-economic public services in Slovenian law are in essence economic, i.e. market activities. The author further concludes that the separation of activities of public institutions into public services and market activities is not adequate, since substantive distinction between them is impossible. He also criticises the decision of the Slovenian Constitutional Court in the case U-I-194/17, where the court missed the opportunity to clarify the question of economic and non-economic activities in the scope of "non-economic" public services, as this term is used in Slovenian law.
Keywords: economic and non-economic activity; gospodarska in negospodarska dejavnost; javne službe; market activity of public institutions; public services; services of general interest; storitve splošnega pomena; tržna dejavnost javnih zavodov